Profil Pasien Kanker Paru Primer yang Dirawat Inap dan Rawat Jalan di Rumah Sakit Umum Daerah Dr Soetomo Surabaya : [Profile of Primary Lung Cancer Patients in Dr. Soetomo General Hospital Surabaya] - Muhammad Rudy Chairudin; Isnin Anang Marhana; Dyah Erawati (Jurnal Respirasi, 2019)
Background: Lung cancer is still one of the biggest contributors to cancer deaths. GLOBOCAN in 2012 reported that lung cancer causes 30% of cancer deaths in men and 11.1% in women. Objective: The purpose of this study was to determine the profile of lung cancer in the General Academic Hospital Dr. Soetomo.Method: This research uses a descriptive observasional type by taking one time  through medical record data from 186 primary lung cancer patients in Dr. Soetomo Hospital during January to December 2017. Results: Men (70.4%) more than women (29.6%). The most age group is 51-60 years (35.5%). Men and women suffer the most from adenocarcinoma (78.6% and 87.3%). Most jobs are private employees (38.2%). Most education is high school (70.4%). The most of patients live in East Java (97.3%) and the most specific are in Surabaya (39.2%). Most Histopathology is non-small cell lung cancer (95.9%) with adenocarcinoma is the most common type (81%). Lung cancer with small cell and non small cell type are mostly found in stage IV (82.3%) and extensive stage (3.8%). Local metastases are mostly found in the contralateral lung (58.1%), and most distant metastases in the brain organ (66.7%). The most common complication is pleural effusion (42.5%). Shortness of breath is the most common symptom (59.1%). The most widely used chemotherapy drug is pemetrexed-cisplatin (17.1%). Conclusion: Primary lung cancer patients at Dr. Soetomo Regional Academic Hospital majority of men aged 51-60 years. Most local metastases are in the contralateral lung and distant metastases in the brain. Most complications are pleural effusion.